Pengurusan projek PPEK di Baram, Sarawak - Anthony Tanjong, anak Ambi. (Universiti Malaysia Sarawak, (UNIMAS), 2002)
This study is as attempt to evaluate rural communities project. It is also to view Program Peningkatan Ekonomi Kampung (PPEK). It also study project management and team work. The location for survey is Iban villages at Baram district.